Notary Role in Implementing Acquisition of Assets Debtors (AYDA) To Overcoming Bad Debt Settlement (Case Study at Banking Pati Regency) - Hartini Hartini; Lathifah Hanim (Jurnal Akta, 2020)
The aim of research to determine: (1) Implementation of foreclosed assets by the Bank; (2) The role of the Notary in the Implementation of foreclosed assets; and (3) Obstacles and solutions in the implementation of foreclosed assets by the Bank. The data used in this research is secondary data in the form of primary legal materials, legal materials, secondary, tertiary and data.Based on the results of data analysis concluded that: (1) Implementation of foreclosed assets is done through voluntary surrender by the debtor, the auction of mortgage, and the legal process; (2) The role of the Notary in the Implementation of foreclosed assets through legal acts compensated by making the Sale and Purchase Agreements; and (3) Obstacles to the implementation of foreclosed assets derived from: (a) the debtor, the debtor does not happen because the credit cooperative in completing the stalled; (B) a third party, in this case mainly the owners of land and buildings pledged by the debtor to the bank as a creditor. Third parties often take the fight at the time of the execution of the collateral to be taken over; and (c) the country through the provision of legislation. Solutions to overcome these obstacles through the effectiveness and efficiency of foreclosed assets.Keywords: Notary; Foreclosed Assets; Credit Los.